Respuesta :

Step-by-step explanation:

Hey, there!!

You can get your answer simply, just remember the two point formula,

Given, the points are (0,2),(8,8).

We have, Formula for two points is,

[tex](y - y1) = \frac{y2 - y1}{x2 - x1} (x - x1) [/tex]

Put all values here,

[tex](y - 2) = \frac{8 - 2}{8 - 0} (x - 0)[/tex]

[tex](y - 2) = \frac{6}{8} (x -0)[/tex]

[tex](y - 2) = \frac{3}{4} (x - 0)[/tex]

multiply (y-4) by 4 and (x-0) by 3.

[tex](4y - 8) = 3x[/tex]

Bringing 4y and -8 on same side of 3x.

[tex]0 = 3x - 4y + 8[/tex]

[tex]or \: 3x - 4y + 8 = 0[/tex]

Therefore, 3x-4y+8=0..... is the required equation.

Hope it helps..